Halal product awareness and trust from students perspectives: The role of gender - Shafariah, Hanuna; Gofur, Abdul (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This research aims to investigate the impact of awareness of halal products on consumer trust levels by considering the moderating role of gender. The research method involves regression analysis to evaluate the relationship between these variables. The research sample consisted of 126 respondents randomly selected from the consumer population. The main findings show that awareness of halal products positively and significantly impacts consumer confidence levels. The regression results confirm that the higher the consumer's awareness of the halal product, the higher the consumer's trust in the product. Moderation analysis confirms that female consumers strengthen the positive relationship between awareness of halal products and consumer trust, compared to male consumers.